The Obstacles Faced by Teachers in Online Learning during the Covid-19 Pandemic at Sei Rattan Yapim Taruna Private Vocational Schoolan - Lubis, Yully Yanti (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2022)
Coronavirus disease 2019 (Covid-19) is a new type of coronavirus (SARS-CoV-2). This virus that attacks the human respiratory tract has hit the world since the end of 2019, and Indonesia became one of the countries affected by the Covid-19 virus on March 2, 2020. This covid-19 pandemic has greatly impacted all factors of life, one of which is education. To reduce the spread of this virus, one of the efforts made by the government is to implement an online system in the learning system. This study aimed to determine the obstacles faced by teachers when teaching online at YAPIM TARUNA SEI ROTAN PRIVATE VOCATIONAL SCHOOL. This research is qualitative. Data collection techniques used were online observation and interviews. The subjects of this study were teachers at the YAPIM TARUNA SEI ROTAN PRIVATE VOCATIONAL SCHOOL, with a total number of 19 people. The data analysis technique used data reduction, data presentation, data verification, and drawing conclusions. The results showed that the obstacles experienced by teachers during online learning were the lack of understanding of students when carrying out the online learning process, the lack of motivation of students in participating in online learning, the lack of facilities owned by students when learning online because not all students had smartphones or computers as a learning media, and internet packages that cannot be posessed by all students.